Large-scale determination in exercise-inducible gene expression with DNA microarray technique - Chen, M. S.; Lee, L. C.; Tseng, C. H.; Lee, H. H.; Chui, H. Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the current study was to determine the exercise-responsive gene from a thousands of genes expressed in blood cell with DNA microarray technique. The preliminary result suggests that genes related to oxygen transport could be elevated by exercise training. Since iron plays important role in synthesis of myoglobin, hemoglobin, and mitochondrial electron transport proteins. Coordinated elevation in iron transport system appears to be essential for the exercise training adaptation for enhancing energy metabolism.